Medical outcomes of adolescent live kidney donors. (20th March 2014) - MacDonald, David; Kukla, Aleksandra K.; Ake, Sarah; Berglund, Danielle; Jackson, Scott; Issa, Naim; Spong, Richard; Matas, Arthur J.; Ibrahim, Hassan N.
Abstract Living kidney donation from donors <18 yr of age is uncommon. The majority of donations from adolescents took place several decades ago providing a unique opportunity to study true long‐term consequences of donation. We compared survival, renal outcomes, and rates of hypertension and diabetes among 42 adolescent donors and matched older controls. Adolescent donors were matched with donors 18–30 yr on the following: gender, relation to the recipient, BMI at donation, eGFR at donation, and year of donation. After a mean follow‐up of 31.8 ± 8.0 yr, 94.9% of adolescent donors were alive vs. 93.8% of controls. There was no significant difference in having eGFR (MDRD) <60 mL/min/1.73 m2 (26.1% vs. 40.9%), hypertension (35.9% vs. 39.4%), diabetes (5.1% vs. 12.5%), or proteinuria (15.4% vs. 14.1%): adolescent donors vs. controls for all comparisons. These data suggest that adolescent donors are not at a higher risk of shortened survival, hypertension, diabetes, or proteinuria. Nevertheless, they probably should donate only when other options are exhausted as they have to live with a single kidney for decades and longer follow‐up is needed.